Interview - Meta-Education: The Attempt to Get Beyond a Politicized Conceptual Framework in Philosophy of Education - Burbules, Nicholas; Johnston, James Scott (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2023)
This interview on Meta-Education, published in the Theory and History of Education International Research Group’s Open Monograph Series, is conducted by Prof. Nicholas Burbules of the University of Illinois, Urbana-Champaign with the author, James Scott Johnston. The interview is wide-ranging and discusses topics and issues arising from the monograph. Chief among these include the importance of a philosophy of education that resists dominant political ideologies. The nature of ideologies and their role in politics is also discussed. The importance of resistance in each of the main functions of education – teaching and learning, the curriculum, and schools and schooling – is addressed. Finally, certain ways of introducing students to philosophy of education are critiqued for their subtle invocations of ideology.